EXTRACTION AND LYOPHILIZATION LOW-DENSITY LIPOPROTEINS AND USED IT INSTEAD OF EGG YOLK IN SEMEN EXTENDER OF AWASSI RAMS AND THEIR INFLUENCE IN SPERM ABNORMALITIES STORE AT 5 ° C - & et al., Al-Subaihawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted  to explain the possibility of lyophilization of low – density lipoprotein (LDL)  that is extracted from the egg yolk to be used instead of the egg yolk in  a dilute  semen of Awassi sheep and its  impact on  the rate of deformities of sperm  after stored at 5 ° C for five days. The study  was conducted from September 2015 to February  2016 and in three stages. The first stage started from July until August 2015 in the laboratory of viruses, that is a related Department to the plant protection office. During this stag the (LDL) was extracted  through several sequential steps from fresh egg yolk, and purified and stored in Fastened and steriled vials which are refrigerated until the time of lyophilization. The second stage was conducted  in August  2015 in Al-Kindy company. During  this study the liquid (LDL) was  lyophilized  and kept in steriled and tightly- fostened viols and then was stored in under the  0°C . The  third stage was conducted in the college of Agriculture/ University of Baghdad. In this stage the semen was collected from four of the Awassi rams of the age (2 – 4) years .The semen samples were collected using artificial vagina and the pooled, to remove  the individual differences between the rams. Later on the sample was divided on the experimental treatments evenly 1 ml/ transaction using a dilute Tris with 1:10 dilution ratio. The different concentrations of LDL on the characteristics of semen have also been studied. However; the experiment was conducted from January to February 2016 and during which three concentrations of LDL have been used (3.2 , 4.8 and 6.2%) the transactions T1, T2 , and respectively and the control treatment (20% EY). The improve of the lyophilized LDL has been studied on the different kinds of distortions that effect the sperm at  preservation temperature 5°C, for five consecutive days. Results of the experiment to outweigh LDL transactions in the low proportion of the various distortions that happens to sperm in distortions head swollen to the control group in two days, third, fourth and zero, distortions on other days as well as these transactions excelled in deformation of the tail broken on the fourth day, and in other types of malformations observed failure the presence of significant difference between the control group as in the distortions severed head and tail severed tail twisted as well as the lack of distortions in other types as in distortions tail double moderation bulging and widget, we conclude from the foregoing the possibility of using LDL lyophilized in thinners semen because of its ability in maintaining semen and reduce some types of malformations as well as he did not adversely affect the sperm as it was similar to egg yolk in maintaining sperm if not better.